Prospective phase II study of rituximab with alternating cycles of hyper‐CVAD and high‐dose methotrexate with cytarabine for young patients with high‐risk diffuse large B‐cell lymphoma. (1st October 2013) - Oki, Yasuhiro; Westin, Jason R.; Vega, Francisco; Chuang, Hubert; Fowler, Nathan; Neelapu, Sattva; Hagemeister, Fredrick B.; McLaughlin, Peter; Kwak, Larry W.; Romaguera, Jorge E.; Fanale, Michelle; Younes, Anas; et al.
Summary We conducted a prospective randomized phase II study to evaluate two chemotherapy regimens: (i) rituximab plus hyperfractionated cyclophosphamide, vincristine, doxorubicin and dexamethasone (R‐HCVAD) alternating with rituximab, high‐dose methotrexate, and cytarabine (R‐MA) and (ii) rituximab, cyclophosphamide, doxorubicin, vincristine and prednisone (R‐CHOP) in diffuse large B‐cell lymphoma (DLBCL). This study randomized patients aged ≤60 years with DLBCL and an age‐adjusted international prognostic index ≥2 to R‐HCVAD/R‐MA or R‐CHOP based on a Bayesian adaptive algorithm. Interim analysis of the first 26 eligible patients showed that the complete response rate (CRR) was higher with R‐HCVAD/R‐MA than R‐CHOP (P = 0·03); thus, R‐CHOP arm was closed. In the final analysis, 49 and 10 eligible patients were treated in R‐HCVAD/R‐MA and R‐CHOP arms respectively; CRR were 82% and 60% respectively (P = 0·13); 3‐year progression‐free survival (PFS) rates were 75·7% and 77·8% respectively (P = 0·53). In the R‐HCVAD/R‐MA arm, 3‐year PFS rates in patients aged 46–60 years and ≤45 years were 70·3% and 87·1% respectively (P = 0·13), and the treatment‐associated early mortality rate in patients >45 years was 12%. In conclusion, R‐HCVAD/R‐MA is associated with excellent outcome in patients ≤45 years old. However, in patients >45 years old, R‐HCVAD/R‐MA is associated with unacceptable mortality rates.